The design and implementation of a flexible manufacturing system for a surface mounting production line - Chodos, Mark, Steven (My University, 1990)
The viability of introducing a Surface Mount production line is chiefly determined by the reliability characteristics of the components being used. Surface Mount Technology (SMT) is entirely new and although related to traditional through-hole processes, requires different components, assembly techniques and design methods. The purpose of the literature survey is primarily to determine whether surface mount components meet today's industrial requirements with respect to their manufacturing reliability and availability. A brief review of the evolution of SMT is also presented. This study finds that the implementation of SMT should be given highest priority by manufacturing companies in order to maintain their share of the marketplace. Surface Mount Technology embodies a totally new automated circuit assembly process, using a new generation of electronic comporents: surface mounted devices (SMDs). Smaller than conventional components, SMDs are placed onto the surface of the substrate. From this, the fundamental difference between SMD assembly and convencional through-hole component assembly arises; SMD component positioning is relative, not absolute. When a through-hole component is inserted into a pcb, either the leads go through the hales or they don't. An SMD, however, is placed onto the substrate surface, it's position only relative to the solder lands, and placement accuracy is therefore influenced by variations in the substrate track pattern, component size, and placement machine accuracy. Other factors influence the layout of SMD substrates. For example, will the board be a mixed-print ( a combination of through-hole components and SMDs) or an all-SMD design? Will SMDs be placed on one side of the substrate or both? And there are process considerations like what type of machine will place the components and how will they be soldered? This project describes in detail the processes involved in setting up an SMT facility. A simulation program was developed to verify the viability of these processes. The simulation program was also applied to an existing SMT facility and together with developed optimization software, attempted to identify and resolve some of the major problems. All this was achieved, and the extent to which simulation could be used as an efficient production tool, was highlighted.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering.
Keywords: Surface mount technology; Electronic packaging